Marketing Analysis of Dompet Dhuafa Livestock/Sheep Center Sheep in Deli Serdang District - Syafina, Vera Dila; Siregar, Galih Ari Wirawan (Jurnal Peternakan Integratif, 2024)
The demand for sheep increases every year due to the community's need for sheep for daily consumption as well as for the celebration of Muslim religious holidays.This study aims to determine the form of marketing channels, marketing margins, marketing agency profits, farmer's share, and marketing efficiency of Dompet Dhuafa Livestock Center sheep in Deli Serdang Regency.The research method used was observation through direct interviews with respondents assisted by filling out questionnaires. Sampling was conducted using snowball sampling technique. The research sample was all marketing institutions involved in the marketing of Dompet Dhuafa Livestock Center sheep in Deli Serdang Regency. The results showed that the smallest sheep marketing margin was in channel 1 at Rp. 7000/head and the largest in channel 3 at Rp. 156,450/head. Farmer's share received by Dompet Dhuafa Livestock Center in Deli Serdang Regency was highest in channel 1 at 99.60% (rams) and lowest in marketing channel 3 at 87.84% (ewes). The most efficient sheep marketing channel is in channel 1 with a value of 0.39% (rams) and channel 3 is an inefficient channel with a value of 1.75% (ewes). Marketing channel 1 is considered the most efficient at 0.39% (rams) and 0.61% (ewes) and has the lowest margin value of Rp. 7,000/head of livestock and has the highest farmer's share value of 99.60% (rams) and 99.38% (ewes) which means marketing channel 1 has the best level of efficiency with the lowest margin value and the highest farmer's share value. In conlusion that marketing is more efficient when Dompet DhuafaÂ  directly sell sheep to consumers and sales value of rams is higher than ewes